Efficient in vitro gene therapy with PEG siRNA lipid nanocapsules for passive targeting strategy in melanoma. Issue 11 (18th October 2014) - Resnier, Pauline; LeQuinio, Pierre; Lautram, Nolwenn; André, Emilie; Gaillard, Cédric; Bastiat, Guillaume; Benoit, Jean‐Pierre; Passirani, Catherine
Abstract Small interfering RNA (siRNA)‐mediated gene therapy is a promising strategy to temporarily inhibit the expression of proteins implicated in carcinogenesis or chemotherapy resistance. Although intra‐tumoral administration can be envisaged, studies currently focus on formulating nanomedicines for intravenous injection to target tumor sites as well as metastases. The development of synthetic nanoparticles and liposomes has advanced greatly during the last decade. The objective of this work consists in formulating and optimizing the encapsulation of siRNA into lipid nanocapsules (LNCs) for efficient gene therapy to target melanoma cells. SiRNA LNCs were prepared from DOTAP/DOPE lipoplexes, and the siRNA amount and lipid/siRNA charge ratio were assayed to improve the stability and the encapsulation yield. Cryo‐TEM imaging of the siRNA lipoplexes and LNC morphology revealed specific organization of the siRNA DOTAP/DOPE lipoplexes as well as specific lipid microstructures that can be eliminated by purification. No cytotoxicity of the siRNA LNCs against the melanoma SK‐Mel28 cell line was observed at concentrations of up to 500 ng/mL siRNA. In vitro siRNA transfection experiments, compared to Oligofectamine™, demonstrated interesting targeted gene silencing effects. Finally, complement activation assays confirmed the feasibility of the PEGylation of siRNA LNCs as part of a passive targeting strategy for future in vivo melanoma‐ and metastasis‐targeting experiments.